Development of Inquiry-Based Interactive Multimedia to Improve Student Learning Outcomes of Pancasila Education Lessons - Riska Armianti; Sri Yunita; Retno Dwi Suyanti; Surya Dharma; Daulat Saragi; Aman Simare-mare (Dinasti International Journal of Education Management And Social Science, 2025)
In the learning process in the classroom, the conventional learning model is still used, where the teacher only plays the role of conveying information, while the students are passive listeners. This study aims to produce inquiry-based interactive multimedia that has been tested for media feasibility and has been proven effective in improving cognitive, affective, and psychomotor learning outcomes in fifth-grade students of Pancasila education at SDN 056425 Damar Seratus. The type of research used is Research and Development (R&D), commonly referred to as research and development. The development design in this study uses the Analysis Design Development Implementation Evaluation (ADDIE) model. The subjects of the research are fifth-grade students of SDN 056425 Damar Seratus. The results of the validation by media experts, design experts, material experts, education practitioners, and the results of field trials (individuals and small groups) indicate that the developed media products are suitable for use and categorised as very good. The Inquiry-Based Interactive Multimedia product in the form of Articulate Storyline 3 developed is also effective for use. The effectiveness of the developed media products is evidenced by the N-Gain test, which yielded a result of 0.6, and the hypothesis test, which yielded t-count = 8.286 and t-table = 1.705, thus t-count > t-table, leading to the acceptance of Ha and rejection of H0. In addition to being effective in improving cognitive learning outcomes in students, this inquiry-based interactive multimedia in the form of articulate storyline 3 is also effective in changing affective and psychomotor aspects in students. In the affective aspect, an average score of 44.9 was obtained with an average score percentage of 89.9%, this proves that the affective aspect of students has changed significantly with the very good category. In the psychomotor aspect, the results were obtained with an average score of 37.7 with an average score percentage of 75.4%, this proves that the psychomotor aspect students has changed significantly with the good category.